2015
DOI: 10.1016/j.biortech.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the ozone pretreatment of wheat straw

Abstract: Wheat straw is a potential feedstock in biorefinery for sugar production. However, the cellulose, which is the major source of sugar, is protected by lignin. Ozonolysis deconstructs the lignin and makes cellulose accessible to enzymatic digestion. In this study, the change in lignin concentration with different ozonolysis times (0, 1, 2, 3, 5, 7, 10, 15, 20, 30, 60min) was fit to two different kinetic models: one using the model developed by Garcia-Cubero et al. (2012) and another including an outer mass trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In Experiment 3, micronised wood powder was irradiated with an ozone lamp to examine the decomposition of lignin. It has been reported that exposure of lignocellulose to ozone decomposed it to lignin [20,21,30]. Because the mixing for preparation to expose micronised wood powder to a sterilisation lamp (254 nm) and ozone gas was performed manually, decomposition of lignin might have been insufficient in this study.…”
Section: A-cmentioning
confidence: 91%
See 1 more Smart Citation
“…In Experiment 3, micronised wood powder was irradiated with an ozone lamp to examine the decomposition of lignin. It has been reported that exposure of lignocellulose to ozone decomposed it to lignin [20,21,30]. Because the mixing for preparation to expose micronised wood powder to a sterilisation lamp (254 nm) and ozone gas was performed manually, decomposition of lignin might have been insufficient in this study.…”
Section: A-cmentioning
confidence: 91%
“…Furthermore, this study confirmed that irradiation of micronised wood powder by an ozone lamp was superior to that of a UV lamp (254 nm) for accelerating volatile fatty acid production (Experiment 4). In the combination of both UV wavelengths, 254 nm UV would play a role to stimulate generation of active oxygen (free radicals) by ozonolysis [30]. Thus, an ozone lamp consisting of UV wavelengths of 254 nm and 185 nm will be effective to elicit the photochemical decomposition of lignin.…”
Section: A-cmentioning
confidence: 99%
“…One of those methods is the application of ozone gas (O 3 ) on agricultural products, an oxidation technique for the sanitization of postharvest grain contaminants (Chen et al, ; El‐Desouky, Sharoba, El‐desouky, El‐Mansy, & Naguib, ; Sahab, Hassanien, El‐nemr, Abdel‐alim, & Mosaad, ; Trombete et al, ). However, the use of ozone could also harm the physicochemical properties of grains and seeds by promoting oxidative degradation of the nutrients, as related by Bhattarai et al () and Gozé, Rhazi, Pauss, and Aussenac () consequently, can influence some thermal properties during drying, by its effect on the surface of the product.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat straw is one of the most abundant agricultural straws in the world, of which the total production was approximately 9.31 × 10 11 kg in 2014 (Bhattarai et al 2015). However, most of the wheat straw in China was directly burnt; only a small fraction was used in the papermaking industry, animal feed industry, and fertilizer industry (Qiu et al 2017).…”
Section: Introductionmentioning
confidence: 99%